Libraria interior in the Collegium Maius – present and past - Kulig, Anna (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2016)
This paper presents the story of the transformation of the interior of the library in the Collegium Maius in Kraków, from the very founding in the 16th century until today, based on various sources. A different approach to the interior arrangement was proposed, relating in its nature to the medieval library.